Post-Encounter Tourism Experience in Saudi Arabia : Sentiment Analysis of Online Reviews - Alsaati, Tasneem (Indian Journal of Marketing, 2025)
Purpose : The purpose of this research was to identify the key themes present in the consumer online reviews for carefully selected sites in Riyadh, Saudi Arabia, to highlight the key aspects that tourists and visitors experience and express at the post-encounter stage of their tourism experience, and the factors they relied on when they evaluated their experience. Design/Methodology/Approach : This research applied the approach of sentiment analysis to online review text extracted from Google Maps for the top tourism sites in Riyadh, Saudi Arabia. In this study, the top 1,000 high-rated and low-rated reviews for each tourism site were extracted and analyzed descriptively by using the NVIVO software. Findings : The results revealed five themes present in both high and low-rated reviews, namely consumer experience, service elements, location, consumer characteristics, and future intentions. Managerial Implications : Managers would be able to develop effective strategies to leverage the positive impacts of online reviews, the business outcomes, and to help tourism site managers in allocating resources to improve ratings and tourists’ comments. Originality/Value : As consumers increasingly rely on online resources to formulate their purchase decisions, researchers and marketers need to understand the consumer experience expressed through consumer-generated content (online reviews). Given the growing attention towards tourism in Saudi Arabia, the issuance of tourism visas, and the race to accomplish the agenda of the Saudi Vision 2030, it becomes highly important to carefully assess the consumer experiences in this domain.